Some recent developments in secondary education in Great Britain with special reference to technical education - Paulin, D. M. (Statistical and Social Inquiry Society of Ireland, 1958)
No apology is needed for addressing this society on an educational topic. In the 1830's Dr. Kay, later Sir James Kay-Shuttleworth, wrote a pamphlet, ?The Moral and Physical Conditions of the Working Classes employed in the Cotton Manufacture in Manchester?. This pamphlet inspired a number of influential Manchester citizens to found the first Statistical and Social Inquiry Society. Dr. Kay believed that education could be one of the most important means of overcoming the squalor and degradation prevalent in industrial cities, and he devoted his life to developing an efficient elementary school system. Education to him was important as an instrument of social change.
Read before the Society in Belfast on February 20th, 1958
Keywords: Secondary education; Technical education; Human capital; 314.15